1997
DOI: 10.2307/2265878
|View full text |Cite
|
Sign up to set email alerts
|

Stable Isotopes in Animal Ecology: Assumptions, Caveats, and a Call for More Laboratory Experiments

Abstract: For decades, plant ecologists have used naturally occurring stable isotope ratios to disentangle ecological and physiological processes. The methodology can also become a very powerful tool in animal ecology. However, the application of the technique relies on assumptions that are not widely recognized and that have been rarely tested. The purpose of this communication is to identify these assumptions, to characterize the conditions in which they are not met, and to suggest the laboratory experiments that are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
546
0
15

Year Published

1999
1999
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 382 publications
(571 citation statements)
references
References 28 publications
10
546
0
15
Order By: Relevance
“…Stable isotope analysis is a fundamental tool in food web studies yet comes with a number of well-documented caveats (Gannes et al 1997; Vander Zanden and Rasmussen 2001; Mateo et al 2008). For example, numerous studies have indicated how inconsistencies in 13 C and 15 N values for the same species can arise through diVerences in preanalytical protocols (Feuchtmayr and Grey 2003;Sarakinos et al 2002;Syväranta et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Stable isotope analysis is a fundamental tool in food web studies yet comes with a number of well-documented caveats (Gannes et al 1997; Vander Zanden and Rasmussen 2001; Mateo et al 2008). For example, numerous studies have indicated how inconsistencies in 13 C and 15 N values for the same species can arise through diVerences in preanalytical protocols (Feuchtmayr and Grey 2003;Sarakinos et al 2002;Syväranta et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been considered that the cell walls of unicellular organisms are difficult to digest by a range of species (Becker, 2007), results from the present study indicate that a high proportion of dietary nitrogen was incorporated from TY in animals fed on all mixed diets. In this context, it has been pointed out that animal tissue often does not reflect the bulk isotopic composition of the diet, but the isotopic composition of the constituents of the diet from which the tissue was biosynthesized (Gannes et al, 1997 http://www.sciencedirect.com/science/article/pii/S0044848615302544…”
Section: Growth and Survivalmentioning
confidence: 99%
“…Stable isotope studies have generated inferences about trophic relationships (O'Reilly et al 2002), nutritional conditions (Gannes et al 1997(Gannes et al , 1998, and even the migratory origins of community members (Hobson 1999;Rubenstein and Hobson 2004). Processes that cycle nutrients within and between biological compartments aVect the isotopic composition of recipients (Criss 1999;Rubenstein and Hobson 2004).…”
Section: Introductionmentioning
confidence: 99%
“…with seasonal or stochastic changes in nutrient source and quantity), ecological-level predictions can falter (O'Reilly et al 2002;Post et al 2000). Reviews repeatedly call for more careful characterization of isotopic baselines in ecological studies (Gannes et al 1997;Lorraine et al 2002;O'Reilly et al 2002;Post 2002;Rubenstein and Hobson 2004).…”
Section: Introductionmentioning
confidence: 99%